2023
DOI: 10.1039/d2ce01616h
|View full text |Cite
|
Sign up to set email alerts
|

Discerning subtle high-pressure phase transitions in glyphosate

Abstract: The common garden herbicide glyphosate, N-(phosphonomethyl)glycine (glyphosate), has been studied between ambient pressure and 5.17 GPa using single crystal x-ray diffraction. Glyphosate forms a structure composed of layers parallel to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The latter study had supported the use of the SMD-B3LYP-D3/6-311++G(2d,2p) as the most reliable level of calculation to predict accurately the structure of Glyph monomer and its deprotonation reaction sites in water solution. Regarding Glyph dimers, they have received some theoretical attention too, 47,63 although much less than the monomer. Previous quantum chemical studies on Glyph dimers were restricted to protonbound Glyph dimer in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study had supported the use of the SMD-B3LYP-D3/6-311++G(2d,2p) as the most reliable level of calculation to predict accurately the structure of Glyph monomer and its deprotonation reaction sites in water solution. Regarding Glyph dimers, they have received some theoretical attention too, 47,63 although much less than the monomer. Previous quantum chemical studies on Glyph dimers were restricted to protonbound Glyph dimer in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Previous quantum chemical studies on Glyph dimers were restricted to proton-bound Glyph dimer in the gas phase. 47 An other recent investigation 63 motivated by the observation of two high pressure phase transitions by Raman spectroscopy, allowed the prediction of a new crystal structure of Glyph consisting of periodic repetition of pairs of zwitterion forms sustained by N–H⋯O H-bonds using crystal modeling. Moreover, other theoretical studies 57,58 concluded that dimers of Glyph are stabilized by divalent and trivalent metal cations, which is feasible in biological systems.…”
Section: Introductionmentioning
confidence: 99%